Rekonstruksi Hak Khiyār sebagai Standar Minimum Retur–Refund dalam Jual Beli Ritel di Indonesia: Harmonisasi Khes dan UU Perlindungan Konsumen: Reconstructing the Right of Option (Khiyar) As A Minimum Return-Refund Standard in Indonesian Retail Trade: Harmonizing Islamic Economic Law (Khes) and Consumer Protection Law - Ahmad Wahyudi; Bagas Heradhyaksa; Kholid Irfani; Pas Inggrid Pamesti; Wawaysadhya (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2026)
Retail transactions in Indonesia frequently apply “no return/no refund” policies through standard terms, creating tension between effective consumer remedies and contractual certainty. This article aims to reconstruct khiar rights under the Indonesian Compilation of Sharia Economic Law (KHES) as a minimum return–refund standard that is compatible with the Consumer Protection Law (UUPK). Using a doctrinal (normative) legal method, the study employs a statute approach to examine UUPK and KHES, a conceptual approach to operationalize khiar (Syarṭ, ru’yah, and ‘aib) as a remedial mechanism, and a harmonization/legal-policy approach to design an implementable standard. The results propose a minimum standard built on six parameters: scope, valid grounds (defect/’aib, mismatch/ru’yah, trial period/Syarṭ), tiered time windows, proportionate evidentiary requirements, remedy hierarchy (repair/replace/refund), and limited exceptions with alternative remedies. The discussion shows that blanket “no return/no refund” clauses are normatively problematic when they eliminate remedies for defect or mismatch, while structured limitations remain permissible to prevent moral hazard and ensure business certainty. The article recommends adopting a model clause and a minimum SOP (complaint–verification–decision–remedy–recording) as auditable compliance instruments for Indonesian retail.